PENGEMBANGAN MAJALAH EKONOMI (MAKOMI) TERINTEGRASI NILAI ISLAM SEBAGAI MEDIA PEMBELAJARAN SMA NEGERI 4 METRO - Silpina Silpina; Meyta Pritandhari (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
Learning media as an important element in the learning process because when viewed from the function of learning media is as a tool in the learning process. Learning media are only limited to books, powerpoints and blackboards so that students are less enthusiastic in the learning process. So we need learning media that can attract the attention of students such as Economic Magazine with a practical form so that students can be more enthusiastic in learning and understanding the material contained in economic learning materials.The development model used is the ADDIE model which includes several stages including: Analysis, Design, Development, Impementation, and Evaluation. Based on the results of the development of the Integrated Economic (Makomi) Magazine Islamic values as a learning medium it is known that the results of the recapitulation of data that have been done, by the magazine design experts have met the criteria very well with an average score of 84%, by the magazine material experts have met the criteria very worthy with a score an average of 97%, by magazine linguists already fulfilling very decent criteria with an average score of 97%, and by Islamic magazine experts fulfilling very decent criteria with an average score of 95% then the resulting product has become a valid product. Furthermore, the practicality test by students of class XI IPS of SMA Negeri 4 Metro get very decent criteria with an average score of 83%, the resulting product has become a practical product. Thus it can be concluded that the economic magazine (makomi) integrated with Islamic values is a valid and practical learning media for use in the learning process.